KELAYAKAN PEMANFAATAN MEDIA PEMBELAJARAN BIOLOGI YANG DIGUNAKAN PADA MATERI PLANTAE KELAS X SMA NEGERI 2 KENDARI - Kadar, Alviana; La Fua, Jumarddin; Rosmini, Rosmini; Nurlila, Ratna Umi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Learning media are an essential element in the learning process. Innovative learning certainly has a significant impact on students' interest and motivation in learning. This study aims to determine the feasibility of producing leaflets of plants used in religious traditions as learning media on plantae in Class X Senior High School (SMA Negeri) 2 Kendari. This study is descriptive. Data collection was conducted using validation instruments. Four validators carried out validation. Two validators were lecturers from the Faculty of Tarbiyah and Teacher Science, while the other two were biology teachers at SMA Negeri 2 Kendari. Data on the feasibility of leaflet teaching materials on plant material is declared